PERFORMANCE AND MEAT FATTY ACID PROFILE IN MIXED SEX BROILERS FED DIET SUPPLEMENTED WITH FERMENTED MEDICINAL PLANT COMBINATIONS - A. B. M. Rubayet Bostami; M. S. K. Sarker; Chul-Ju Yang1 (Journal of Animal and Plant Sciences, 2017)
`Efficacy of fermented Salicornia herbacea L. and Houttuynia cordata Thunb.(FSH) on performance and meat quality in broilers was assessed. Following completely randomized design 240 day old mixed sex Ross 308 broiler chicks were randomly allocated to five treatments with six replications with eight birds in each. Dietary treatments were: control (corn-soybean meal based basal diet); ABT (Basal diet + 0.05% oxytetracycline); and FSH1 (Basal diet + 0.5% FSH), FSH2 (Basal diet + 1.0% FSH) and FSH3 (Basal diet + 2.0% FSH). Dietary supplementation had no significant negative impact on performance and relative organ weight; however, mortality and abdominal fat was substantially reduced after FSH and ABT supplemented birds relative to control (P<0.05). Breast muscle crude protein content was higher whereas crude fat content was lower in FSH2 group in comparison to control (P<0.05). A substantial diminution was observed in the average meat TBARS value of FSH and ABT group compared to control (P<0.05). Among the breast meat fatty acids, sum of SFA content was down trended whereas sum of PUFA, omega-3 and omega-6 PUFA content was elevated in FSH2 compared to control (P<0.05). Overall, present findings indicated that FSH supplementation was beneficial regarding nutritional aspects of broiler meat where FSH2 found suitable.
Keywords: Fermented Salicornia herbacea L. and Houttuynia cordata Thunb.; Growth Performance; Meat fatty acids; Broilers